2016
DOI: 10.28945/3429
|View full text |Cite
|
Sign up to set email alerts
|

Contingent Faculty Perceptions of Organizational Support, Workplace Attitudes, and Teaching Evaluations at a Public Research University

Abstract: This research examines contingent faculty's perception of organizational support, workplace attitudes, and Student Ratings of Teaching (SRT) in a large public research university to investigate their employee-organization relationship. According to t-tests and regression analyses for samples of 2,229 faculty and instructional staff who answered the survey and had SRT data (tenured and tenure-track faculty: 1,708, 76.6% of total; contingent faculty: 521, 23.4% of total), employment relationship of contingent fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…51 For instance, Cha and co. indicated that employee's perception of workplace support and working environment affect employee organizational relationship. 52 It has been predicted by human capital theory that knowledge, skills and competence that are additionally accumulated during internship result in employability and higher renumeration compared to those who do not undertake internship. 53 This assertion was supported that internship enhances the employability of graduates and lead to higher earnings.…”
Section: Students Perception Values and Outcomes Regarding Internshipmentioning
confidence: 99%
“…51 For instance, Cha and co. indicated that employee's perception of workplace support and working environment affect employee organizational relationship. 52 It has been predicted by human capital theory that knowledge, skills and competence that are additionally accumulated during internship result in employability and higher renumeration compared to those who do not undertake internship. 53 This assertion was supported that internship enhances the employability of graduates and lead to higher earnings.…”
Section: Students Perception Values and Outcomes Regarding Internshipmentioning
confidence: 99%
“…The employment of contingent teachers in higher education institution is prevalent due to new staffing patterns in academia [1]. The percentage of fulltime, non-tenure track faculty has doubled from 18.6% to 37.6% from 1975 to 2007 and it has tripled during the past three decades as nearly 60% of new fulltime faculty appointments are now under temporary contracts [2]. Contingent faculty, also known as adjuncts, or non-tenure track faculty, represent two thirds of all faculty members in higher education in the United States [1].…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars have suggested that less than equitable salaries and working conditions can result in relatively lower levels of overall organizational commitment for affected employees [6] and comparatively, contingent faculty members fall into these categories. A growing number of studies have reported negative aspects of contingent faculty's lives such as depression, anxiety, and stress at work due to their contingent employment status, on the other hand, another line of research suggested that the influences of contingent faculty were not always negative [2].…”
Section: Introductionmentioning
confidence: 99%